SCHOOL STRATEGIES IN REBUILDING THE CHARACTER OF SD/MI STUDENTS POST ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Subiyantoro Subiyantoro (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
The character and attitude of students is a very essential thing in education. The nature of education is not just transferring knowledge but must be able to change behavior or character for the better. The purpose of this study is to reveal how the teacher's strategy in fostering the character of students during online learning in the scope of SD/MI in the Kalibawang Kulon Progo area. This research was conducted using a qualitative approach, namely by collecting data at several State Elementary Schools (SDN) and Madrasah Ibtidaiyah (MI) Ma'arif Kalibawang Kulon Progo, Yogyakarta, as well as various sources such as scientific journals, books, and other documents related to analysis of online learning and its impact on the development of attitudes and character of SD/MI students. The results of this study found that online learning is the best alternative as a breaker in the chain of the spread of the Covid-19 outbreak in schools, but still leaves other educational problems, namely the decline in student enthusiasm for learning, the decline in students' personality characters, and not achieving the subject matter completely. In rural areas (Kalibawang), Kulon Progo, there are several factors that lead to a decline in the personality character of students, including the teacher's lack of intense monitoring of student development due to online learning, the economic condition of the community, namely parents who are busy making a living so that children are not monitored. good educational development, as well as free association children can interact with whoever they want, so it affects the pattern of the character. Therefore, to overcome this, the school rolled out several programs, as well as building communication and cooperation with the parents of students to jointly monitor and supervise the growth and development of their children's education.